Implementasi Google Maps API pada Sistem Informasi Geografis Pemetaan Sekolah Dasar - Brandon, Brandon; Antonius, Antonius; Willay, Thommy (MDP Student Conference, 2025)
This research discusses the importance of a web-based geographic information system (GIS) in supporting the provision of complete and integrated information for elementary schools in Pontianak City District. The goal of this system is to create an interactive and user-friendly platform to present data on school locations, profiles, facilities, and other relevant information. This study uses Unified Modeling Language (UML) as the technique for system analysis and design, and the waterfall model as the system development approach. The system includes features such as interactive maps, data required to support decision-making regarding elementary schools, comparisons based on criteria, and the integration of geographic data managed through a secure database management system. The research develops and implements a web-based information system designed to map the locations of elementary schools in the area. The results of this study are expected to improve the efficiency of mapping and provide valuable information for the community and stakeholders in planning educational policies, as well as developing a responsive and effective system.